Ecological crises of the capitalocene: a study on Colleen Murphy’s the breathing hole - Pal, Supthita; Pannikot, Dhishna (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present paper seeks to lay bare how the grim realities of settler colonialism and petro-capitalism have a tolling effect on the indigenous ways of life. The present era, termed the 'Anthropocene' or'Capitalocene,' asit isthe capitalist concern of some of the privileged anthropos that inflict socio-economic and ecological injustices on earth, heralds the birth of cautionary literature that deconstructs anthropocentric fixation to purge the earth off the catastrophic impacts of rapacious human activities. In order to examine how capitalism and its resultant climate emergency have spurred environmental activists and authors to reflect upon this theme, the paper undertakes a close textual analysis of The Breathing Hole (2020) by Colleen Murphy (b. 1954), a contemporary Quebecois playwright. By employing indigenous ecocriticism and non-human turn in literary studies, the study examines how the playwright jettisons the standardised category of the Anthropos by prioritising the non-human character, Angu’ruaq, an anthropomorphised polar bear. Attempts have been made to highlight how the capitalist motive of the neo-colonial agents leaves a breach in the fabric of the succouring connection between the indigenous Inuit existence and the non-human beings in the Nunavut territory of the Canadian Arctic. The findings of the paper demonstrate how the playwright approaches contemporary eco-crisis using indigenous ecodrama.